2014
DOI: 10.1352/1944-7558-119.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Employment Outcomes of Transition-Aged Adults With Autism Spectrum Disorders: A State of the States Report

Abstract: The primary purpose of this study was to evaluate the employment outcomes of transition-aged adults with autism spectrum disorders (ASD) served by vocational rehabilitation services (VR) over the last 10 years by state. A secondary purpose was to compare employment outcomes of individuals with ASD to those of the overall transition-aged population served by VR for the same time period. Although there was variability both within and among states, the results of this study indicate that, over time, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 13 publications
3
71
0
3
Order By: Relevance
“…Burgess and Cimera (2014) reported that the hours worked per week by young adults with ASD were fairly stable, ranging from 22 to 26 h, and their mean weekly wage over the past decade ranged from $175 to $216. However, these figures were among the lowest in the VR system (average weekly working hours for people in VR system ranged from 29 to 32 h, average weekly earnings ranged from $271 to $322).…”
Section: National Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgess and Cimera (2014) reported that the hours worked per week by young adults with ASD were fairly stable, ranging from 22 to 26 h, and their mean weekly wage over the past decade ranged from $175 to $216. However, these figures were among the lowest in the VR system (average weekly working hours for people in VR system ranged from 29 to 32 h, average weekly earnings ranged from $271 to $322).…”
Section: National Datasetsmentioning
confidence: 99%
“…Although the VR system has a long history of serving people with physical disabilities, it has not been prepared for meeting the needs of emerging service seekers with ASD (Burgess and Cimera 2014;Howlin 2013;Taylor and Seltzer 2011;Wehman et al 2014). A rapidly increasing number of transition youth and adults with ASD have started seeking services from the VR system in recent years (Cimera and Cowan 2009;Migliore et al 2014).…”
Section: Vocational Servicesmentioning
confidence: 99%
“…As young children with ASD and ID age, there will undoubtedly be an increase in young adults in need of support when they no longer qualify for services under Individuals with Disabilities Education Act (Burgess & Cimera, 2014). Some estimate an increase of 230% in the number students with ASD making the transition to adulthood over the next eight years .…”
Section: Introductionmentioning
confidence: 99%
“…Through customized employment, and despite ongoing challenges, an increasing number of people with disabilities have achieved integrated competitive employment including those with autism and behavioral/mental health challenges (Burgess & Cimera, 2014;Hall, Butterworth, Winsor, Gilmore, & Metzel, 2007;Hendricks, 2010;McDonough & Revell, 2010;Rogers, Lavin, Ran, Gantenbein, & Sharpe, 2008;Wehman et al, 2014;Wehman et al, 2016). Nonetheless, some people with disabilities still remain un-or underemployed because of the lack of job openings for which they are well-suited.…”
Section: Entrepreneurship As a Means Of Customized Employmentmentioning
confidence: 99%